Validación de la Cartilla Educativa Digital Camaleón Sonriente Cuida Tus Dientes, Como Estrategia de Motivación en Salud Oral Para Niños (2021)
Introduction: In Colombia, the prevalence of oral diseases is quite high, coming to believe that all people have experienced diseases at some point in their life. Children register high numbers of diseases at the oral level, this due to the fact that their oral hygiene practices are quite deficient. According to research, the high prevalence and incidence of diseases can be prevented. Oral health education is considered one of the pillars of preventive dentistry, which is given through several strategies, among them, the educational booklets are informative brochures that include the minimum contents, in a clear, concise and graphic way. of the treated topic. Validity explores the degree to which an instrument measures what it should measure, that is, what it has been designed for. In the construction of new materials written with the objective of educating in health and elaborated by health professionals, it is necessary that they be examined to maximize their effectiveness, that is why content validation is important for researchers and health professionals concerned with using more and more reliable and appropriate instruments for a certain population. Objective: To validate the “Smiling Chameleon Take Care of Your Teeth” primer, as a motivational strategy for oral health education, through an evaluation by experts. Materials and Methods: The present descriptive epidemiological study aimed to validate the educational strategy "SMILING CHAMELEON TAKE CARE OF YOUR TEETH", which is used as a motivational tool in oral health for children, using an instrument of data collection (Questionnaire) where different categories were evaluated (sufficiency, clarity, coherence, relevance and design), of each one of the dimensions.